Publications of the Bureau of Catholic Indian Missions, January, 1879 - Brouillet, J. B. A.; Seghers, Charles John (The Bureau, 1879)
[1.] Circular of the Catholic Commissioner for Indian Missions to the Catholics of the United States [1874] -- [2.] Petition of the Catholic Church for the agency of the Chippewas of Lake Superior [1873] -- [3.] Manual of Catholic Indian missionary associations [1875] -- [4.] Catholic Indian schools and churches, missionaries and teachers, their number and cost of their support [1875?] -- [5.] [Manual of Catholic Indian Missionary Associations] [1875] -- [6.] Official construction of President Grant's Indian Peace Policy [1875?] -- [7.] Report of the Treasurer of the Catholic Indian Mission Fund, from January, 1873, to December 1, 1876 / J.B.A. Brouillet [1876]